The Effectiveness of Radio Talk Shows by UNICEF Ethiopia in Increasing Knowledge and Changing Attitudes and Behaviors Around Child Marriage, Female Genital Mutilation, and Gender Equality - Ahmed, Haithar; Westering, Jolanda Van; Shikur, Zemzem; Terefa, Fikereselam Getinet; Challa, Andinet; Sharma, Rachana; Aika, Mona; Brooks, Andrew; Sani, Massimiliano; Maksud, Nankali; Akullu, Harriet; Mabirizi, Joseph (Advances in Social Sciences Research Journal, 2023)
Female genital mutilation (FGM), child marriage (CM), and gender inequality are some practices that are discriminatory and abusive to women and deny them the potential to live better and more inclusive lives. UNICEF in collaboration with other partners have initiated radio talk shows (RTS)in SNNP, Oromia, Somali, and Afar regions with the aim of addressing these issues. This evaluation study assessed the effectiveness of these shows on these matters. The study used a cross-sectional survey approach blended with key informant interviews to interrogate the issue at hand. A stratified cluster sampling method was used to identify 458 subjects to participate in the study. The study found that not many people have been reached by the radio talk shows. Those reached had acquired knowledge/enlightenment and attitude change that is positive towards lowering cases of FGM, CM, and gender inequality. The study thus found radio talk shows to be effective in increasing knowledge and attitude that could bring about social behavior change. It was recommended that UNICEF to scale up RTS into unreached areas to expand the reach hence the impact of the shows on FGM, CM, and gender equality.